Interleukin-6 confers radio-resistance by inducing Akt-mediated glycolysis and reducing mitochondrial damage in cells. (31st October 2019) - Kumari, Neeraj; Das, Asmita; Bhatt, Anant Narayan
Abstract: Interleukin-6 (IL-6)-induced glycolysis and therapeutic resistance is reported in some cell systems; however, the mechanism of IL-6-induced glycolysis in radio-resistance is unexplored. Therefore, to investigate, we treated Raw264.7 cells with IL-6 (1 h prior to irradiation) and examined the glycolytic flux. Increased expression of mRNA and protein levels of key glycolytic enzymes was observed after IL-6 treatment, which conferred glycolysis dependent resistance from radiation-induced cell death. We further established that IL-6-induced glycolysis is activated by Akt signalling and knocking down Akt or inhibition of pan Akt phosphorylation significantly abrogated the IL-6-induced radio-resistance. Moreover, reduction of IL-6-induced pAkt level suppressed the expression of Hexokinase-2 and its translocation to the mitochondria, thereby inhibiting the glycolysis-induced resistance to radiation. IL-6-induced glycolysis also minimized the radiation-induced mitochondrial damage. These results suggest that IL-6-induced glycolysis observed in cells may be responsible for IL-6-mediated therapeutic radio-resistance in cancer cells, partly by activation of Akt signalling.